Easy XML publishing into your enterprise portal sharing the power with non-techies. - Moskovits, Peter
Enterprise portals provide a single interface to aggregated and componentized information. They significantly reduce the navigational issues inherent with Web sites and make it easier to publish information from disparate sources. The basic building blocks of enterprise portals are portlets, which are reusable, personalized Web components displaying content from various data sources.